Development of Outdoor Learning Based of Reforestation Technology Education for Early Natural Disaster Prevention in Elementary School Students - Yeni Sulaeman; Dine Trio Ratnasari; Usep Saepul Mustakim (Jurnal Mamangan, 2025)
This study aims to develop an outdoor learning model based on reforestation technology education in order to improve elementary school students' understanding of early natural disaster prevention. The research method used is Research and Development (R&D) with the Borg & Gall model modified into five stages: needs analysis, design, expert validation, limited trials, and evaluation. The study was conducted in five elementary schools in Lebak Regency with a sample of 150 students. The results showed an increase in student understanding with an average pre-test score of 46.2% to a post-test of 83.7%, with an N-Gain of 0.70 which is considered high. The success rate of planted seedlings reached 78%, indicating the success of QR Code-based monitoring and soil moisture sensors. Supporting factors for this program include school support, community participation, and student enthusiasm, while the main inhibiting factors are limited technological tools and extreme weather conditions. The conclusion of the study shows that technology-based outdoor learning is effective in improving students' understanding of reforestation and early disaster mitigation